Mass to voltage ratio index predicts mortality following TAVI. Issue 6 (3rd February 2022) - Porat, Alon; Gordon, Max; Perlman, Gidon; Planer, David; Danenberg, Haim; Alcalai, Ronny; Leibowitz, David
Abstract: Transcatheter aortic valve implantation (TAVI) is commonly performed in elderly patients with aortic stenosis. Better methods of risk stratification are needed in this population with high morbidity. There is a relatively high incidence of cardiac amyloidosis in this population and high LV mass index (LVMI) to QRS voltage may help identify patients with worse prognosis following TAVI. This retrospective study enrolled consecutive patients who underwent TAVI in our institution between the years 2008–2019. Mass voltage ratio index (MVRi) was calculated as the ratio of LV mass index on echocardiogram to voltage using the Sokolow‐Lyon criteria on 12 lead ECG performed within 3 months before the intervention. Two hundred and fifty‐one patients (mean age 80.8 years, 49% men) were enrolled. One hundred and sixty‐eight (67%) patients were alive at 3 years follow up. MVRi was a statistically significant predictor of 3 year mortality ( p < 0.005). Patients were divided categorically into tertiles based on MVRi score; the "high" group had significantly higher 3‐year mortality ( p < 0.001). In the multivariate model only Euroscore ( p < 0.009) and MVRi ( p < 0.011; OR: 2.32; CI: 1.15–4.964) were statistically significant predictors of mortality. The "high" group had a significantly lower survival rate after 3 years follow up on Kaplan–Meier analysis ( p < 0.001). Our findings suggest that MVRi is a strong, independent predictor of increased post‐TAVI mortality. This may be a simple clinical tool to assist in the assessment of patients prior to before TAVI.